Insights into the sodium storage mechanism of Bi2Te3 nanosheets as superior anodes for sodium-ion batteries. Issue 5 (21st January 2022) - Pang, Simeng; Hu, Zhuang; Fan, Changling; Zhang, Weihua; Cai, Yan; Han, Shaochang; Liu, Jinshui; Liu, Jilei
Abstract : Due to the unique structure of Bi2 Te3, nanosheets (BT-Ns) were fabricated by a self-assembly method. Additionally, the BT-N anode exhibits excellent rate and long-term cyclic performance, delivering 364.0 mA h g −1 at 5 A g −1 after 1200 cycles. Abstract : Although bismuth-based anode materials for sodium-ion batteries (SIBs) have attracted wide attention, their large volume variation hinders their actual applications, especially in Bi2 Te3 systems. In this study, Bi2 Te3 nanosheets (BT-Ns) are fabricated by a novel strategy via a solvent reductive reaction. The elements Bi and Te are spontaneously grown into ultrathin nanosheets because the hexagonal crystal of Bi2 Te3 has a strong tendency to grow horizontally. The crystal structure of the BT-Ns is well developed and the thickness is about 1.42 nm, which can not only offer more active sites but also promote electrical conductivity and the diffusion of Na ions and electrons. It exhibits excellent rate and long-term cyclic performance, delivering 364.0 mA h g −1 at 5 A g −1 after 1200 cycles. The high rate and long-term cyclic performance of the Bi2 Te3 anodes is attributed to the facile design of the 2D nanosheet structure, presenting an effective strategy to construct anodes for SIBs. The sodium storage mechanism of Bi2 Te3 follows a three-step crystallographic phase change of Bi2 Te3, discovered by an in situ X-ray diffraction analysis. The applicability of BT-N anodes in full cells via pairing with Na3 V2 (PO4 )3 cathodes delivers excellent performance (energy density of 107.2 W h kg −1 ) and satisfactory practical applied prospects.